Tax Cuts Starve the Beast! Evidence from Germany - Daniel Stöhlker; Florian Neumeier; Clemens Fuest (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper empirically evaluates how fiscal policy reacts to changes in the government's fiscal situation. Utilizing panel data from the German states covering the period from 1992 to 2011, we assess to what extent exogenous changes in tax revenues affect total public revenues, aggregate public expenditure as well as specific sub-categories of government spending. Applying the narrative approach pioneered by Romer and Romer (2010), we construct a measure of exogenous tax shocks, allowing us to identify the causal effect of tax changes on fiscal policy. Our findings indicate that tax changes trigger expenditure adjustments into the same direction after 2 to 3 years, specifically with respect to spending on governmental administration, health expenditures and spending on infrastructure.
Keywords: E62; H11; H20; H62; H72; 330; Taxation; Fiscal Policy; Tax-Spend; Public Expenditure; Narrative Approach